Trinidad, Port of Spain, a Main Street - (:unkn) unknown (My University, 2010)
A policeman directs traffic on Frederick Street, one of the main streets in Port of Spain.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns-- (name); Frederick Street; Port of Spain; Police; Street-railroads; Stores, Retail